Crystal structure of [5-n-butyl-10-(2,5-dimethoxyphenyl)-2,3,7,8,12,13,17,18-octaethylporphyrinato]nickel(II) - SENGE, MATHIAS (My University, 2015)
The asymmetric unit of the title nickel(II) porphyrin, [Ni(C48H60N4O2)], contains one independent molecule. The average Ni—N bond length is 1.917 (13) A˚ . The molecules are arranged in a closely spaced lattice structure in which neighbouring porphyrins are oriented in inversion-related dimers. The nickel(II) porphyrin is characterized by a significant degree of a ruffled (B1u) conformation with small contributions from saddle (B2u) and wave (y) [Eg(y)], as determined using normal structural decomposition. Disorder in the 2,5-dimethoxyphenyl substituent was modelled over two positions with a 60% occupancy for the major moiety. One of the ethyl groups is also disordered over two positions and was modelled with the major moiety being present in 51.3% occupancy.
PUBLISHED
Keywords: Crystallography